FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN ANEMIA PADA IBU HAMIL DI PUSKESMAS PASEAN PAMEKASAN - Mujib Hannan; Syaifurrahman Hidayat; Cory Nelia Damayanti (Fakultas Ilmu Kesehatan, 2012)
Pragnancy anemia is iron subsantce deficiency, it was national problems reflect social and economic society welfare of the community, and had a big influence on human resources. Cause of directly death can't be fully understood without considering the background, which are medical and non medical, non medical factor in the circumstances reffered to family economic well-being, education, tertiary mother's knowledge, environment, behavior, and family support. That's because they anemia requires serious attention and all those involved in healtcare in the future. The objective of this research is aimed to determine the influence of anemia occurance on pregnant woman in health centers Pasean Pamekasan.The research is a non experimental using cross sectional presented analytically. Accidental sampling using the number through inclusion criteria approach by 53 respondents. Data Analysis using chai square test and logistic regression to determine the factors that influence the anemia occurance on pregnant woman in health centers Pasean Pamekasan.There were significant influence between knowledge level factors on the occcurance of anemia in pregnant woman at health centers with significant degree 0, 006 (<0,05), between mother attitude factors to anemia occurance with significant degree 0,016 (<0,05), and no significant effect between family support factor to anemia occurance on pregnant women with significant degree 0,547 (>0,05). Knowledge level is dominan factors which was influence anemia occurance on pregnant woman by P value as much as p=0,045<0,05.Keyword: anemia occurance, pregnant woman